Kuliah Kerja Nyata Menggerakkan Semangat Olahraga dan Persatuan Jorong melalui Turnamen Voli - Anastasya Br. Sitorus; Arini Pratiwi; Dini Ahada Muharrami; Dalila Husna Raheka; Eri Sakinah Piliang; Loisa Ibesti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is one of the forms of higher education community engagement aimed at encouraging student participation in community development. One of the flagship programs implemented in Nagari Batu Payung, Lareh Sago Halaban District, Lima Puluh Kota Regency, was the Inter-Hamlet Volleyball Tournament. This activity was organized in response to the community's high interest in sports and the need to strengthen social relationships among residents from different hamlets. The purpose of this study was to describe the implementation of the tournament and analyze its role in promoting sportsmanship, community participation, and social cohesion among hamlets. This study employed a descriptive qualitative approach through direct observation, documentation, and field participation during the implementation of the activity. The tournament involved eight teams consisting of seven hamlet representatives, namely Pakan Rabaa, Padang Tangah Sialang, Koto Malintang, Kapalo Bukik, Batu Payuang, Seberang Air, and Lareh Nan Panjang, as well as one team from KKN students. The results showed that the tournament was successfully conducted with active participation from the community. The activity not only served as a sports competition but also functioned as a medium for strengthening friendship, increasing social interaction, fostering sportsmanship, and reinforcing unity among hamlets. Therefore, the Inter-Hamlet Volleyball Tournament can be considered an effective community-based activity in supporting social solidarity and promoting active community engagement in Nagari Batu Payung.